ACUAN PEMBANGUNAN ACEH PASCA TSUNAMI Ke Arah Pembangunan Berasaskan Islam - Sukiman Sukiman (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2010)
Abstract: Reference of Development in the Post-Tsunami Aceh: An Analysis Toward Islamic Based Development. Tsunami disaster occurred in Aceh causes not only in the lost of a great number lives but also in very serious destruction of infrastructure and every aspect of lives. Thus, in post Tsunami, rebuilding Aceh becomes the priority of the government. This article tries to analytically describe various government programs in rebuilding Aceh in the post Tsunami. In such a context, the author argues that besides referring to national development program (Propenas) rebuilding Aceh also refer to the regulation of Qanun of Aceh, a regulation of which constitutes the principles of Islamic teachings to be used as a blue print for rehabilitating and reconstructing in the post-Tsunami Aceh. Kata Kunci: pembangunan, propenas, qanun Aceh